Gospodarka to kobieta – kobiety w życiu gospodarczym Polski – rola, miejsce, wpływ - Kacperska, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The situation of women in the labor market has long been the subject of numerous academic studies and discussions at various levels. This paper touches on the issue of the roles women play in the economy. These roles are related both to the unpaid housework performed by women at home and professional work at different levels (performed either as self-employed workers or as employees in the labor market). The considerations presented in the paper unfortunately corroborate the common conviction that the situation of women in the labor market is worse than men’s. The first group under analysis are housewives, who are frequently unable to make a free decision about whether they should work or stay at home. The second group are professional women who find employment or are self-employed.Women in the former group are frustrated by the fact that they do not generate any income in their household, although their work is in fact extremely valuable. The second group faces the ‘glass ceiling’ phenomenon, finds employment in the so-called pink collar sector, sees a prevalence of women working in the public sector, and faces problems with balancing work and family obligations. The paper also indicates the instruments that could improve the situation of women in economic life in Poland, primarily including flexible forms of employment, improved availability (in terms of price and amount) and quality of child care facilities (nurseries, kindergartens, and others), more extensive activities to promote the equality of the sexes (fighting stereotypes) and more opportunities to share childcare responsibilities (on top of extant legal solutions). It has also been observed that women themselves frequently adapt to fit the stereotypes, that they have lower expectations in terms of remuneration, do not allow themselves to be assertive and become overloaded with responsibilities, and they imprint the stereotypes of social and economic roles of men and women on their children. It is concluded that steps need to be taken to ensure greater appreciation of housework, and to make becoming a housewife a conscious decision rather than a compulsion. As regards women who opt for employment or self-employment, they need to be ensured appropriate remuneration that corresponds to their qualifications, experience and achievements, as well as professional advancement regardless of sex.